2021
DOI: 10.3390/ijerph182111535
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Intervention Using Information and Communication Technology for Older Adults with Mild Cognitive Impairment: A Systematic Review and Meta-Analysis

Abstract: Background: Outside activities have decreased due to the spread of the COVID-19 since 2019; therefore, the need for education using information and communication technology (ICT) for older adults with mild cognitive impairment (MCI) has increased. This study systematically evaluated the effects of cognitive enhancement interventions using ICT on older adults with MCI. Methods: Six electronic databases (CINAHL, Cochrane CENTRAL, EMBASE, PubMed, RISS, and KISS) were searched for relevant articles published from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…This indicates that cognitive training using ICT is more effective than traditional cognitive training. By contrast, a systematic review 19 stated that there was no difference in effectiveness between the ICT‐based intervention and active control groups. In a systematic review, 19 some results of the study, 51 showed that ICT‐based cognitive training was more effective than active control.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…This indicates that cognitive training using ICT is more effective than traditional cognitive training. By contrast, a systematic review 19 stated that there was no difference in effectiveness between the ICT‐based intervention and active control groups. In a systematic review, 19 some results of the study, 51 showed that ICT‐based cognitive training was more effective than active control.…”
Section: Discussionmentioning
confidence: 94%
“…By contrast, a systematic review 19 stated that there was no difference in effectiveness between the ICT‐based intervention and active control groups. In a systematic review, 19 some results of the study, 51 showed that ICT‐based cognitive training was more effective than active control. As technology advances, it has gradually become easier to use and more interesting for older adults with MCI or mild dementia 53–55 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations